2022
DOI: 10.1111/rda.14169
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a method to predict dystocia due to physical imbalance between foetus and maternal pelvis in Japanese black cattle

Abstract: This study aimed to clarify the relationship between the maternal pelvis and calf size in normal and dystocia groups (Experiment 1) and to establish a method to predict dystocia due to physical imbalance between foetus and maternal pelvis before calving based on the parameters found in Experiment 1 (Experiment 2). In Experiment 1, 26 pairs of dams and their offspring were tested immediately after calving, and various parameters of offspring size and maternal pelvis were measured in normal and dystocia cases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Holm et al (2014) measured 484 one-year-old heifers and found that measuring the size of the birth canal, along with other body parameters, can significantly reduce the occurrence of difficult parturitions by eliminating heifers with narrow birth canals. Measurements with a pelvimeter can also be used to determine the spatial relations in the pelvic canals of heifers, and predict the probability of calving difficulty (Bila et al 2021, Maeda et al 2022. In none of these experiments (Nahkur et al 2011, Nogalski and Mordas 2012, Holm et al 2014, Bila et al 2021, Maeda et al 2022, pelvic measurements with the Rica pelvimeter caused pain, suffering or stress in animals, which indicates that they can be considered a useful, reliable and safe management tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holm et al (2014) measured 484 one-year-old heifers and found that measuring the size of the birth canal, along with other body parameters, can significantly reduce the occurrence of difficult parturitions by eliminating heifers with narrow birth canals. Measurements with a pelvimeter can also be used to determine the spatial relations in the pelvic canals of heifers, and predict the probability of calving difficulty (Bila et al 2021, Maeda et al 2022. In none of these experiments (Nahkur et al 2011, Nogalski and Mordas 2012, Holm et al 2014, Bila et al 2021, Maeda et al 2022, pelvic measurements with the Rica pelvimeter caused pain, suffering or stress in animals, which indicates that they can be considered a useful, reliable and safe management tool.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements with a pelvimeter can also be used to determine the spatial relations in the pelvic canals of heifers, and predict the probability of calving difficulty (Bila et al 2021, Maeda et al 2022. In none of these experiments (Nahkur et al 2011, Nogalski and Mordas 2012, Holm et al 2014, Bila et al 2021, Maeda et al 2022, pelvic measurements with the Rica pelvimeter caused pain, suffering or stress in animals, which indicates that they can be considered a useful, reliable and safe management tool.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cervix is an important organ that has to dilate sufficiently at delivery to allow the foetus to transition to extrauterine life (Mee, 2008; Van Engelen et al., 2008, 2009). Although insufficient dilatation of the cervix (IDC) is frequently the cause of dystocia in cattle, there has not been much discussion of this problem in the veterinary literature (Maeda et al., 2022; Mee, 2008; Taverne & Van Der Weijden, 2008; Zaborski et al., 2009). According to traditional understanding, softening and dilatation of the cervix are hormone‐related and are controlled by an increase in placental oestrogens and a decrease in progesterone (P4) (Jainudeen & Hafez, 2000), the latter being almost exclusively of luteal origin in the late pregnant cow (Hoffmann et al., 1979).…”
Section: Introductionmentioning
confidence: 99%